Pengembangan Formula Bahan Infeksi Cendawan sebagai Alternatif Biokontrol Rayap Tanah Coptotermes sp. Development of Infection Material Formula for Fungi as Bio-Control Alternative to Subterranean Termites Coptotermes sp - Titik Kartika; Sulaeman Yusuf; Didi Tarmadi; Arief Heru Prasetyo; Ikhsan Guswenrivo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
Utilization of fungal entomopathogen as biological control agent has been developed in several country, but not in Indonesia. Therefore, the use of biological control agent to control termite need to be done in order that diminish chemical insecticide hazard. In this research, the ability of fungal entomopathogen (Hyphomycetes) identified as Metarhizium anisopliae, Beauveria sp. and Humicola sp. to infect Subterranean termite will be evaluated. The fungi were isolated from Indonesia. The research methods are (i) to sporulate fungi in rice culture media; (ii) to formulate fungal entomopathogen being infection materials; (iii) bioassay of fungal entomopathogen against Subterranean termite by contact method. The result of bioassay show that the three fungi (Humicola, M. anisopliae and Beauveria) are able to kill termite in 14 days of observation day. Primarily, M. anisopliae has generate termite’s mortality almost similar to Humicola sp. i.e higher than 60 %, in other side Beauveria just affect termite’s mortality lower than 60 %.